Decorin and biglycan immunolocalization in non‐villous structures of healthy and pathological human placentas. Issue 5 (17th January 2014) - Borbely, Alexandre U; Daher, Silvia; Ishigai, Marcia M; Mattar, Rosiane; Sun, Sue Y; Knöfler, Martin; Bevilacqua, Estela; Oliveira, Sergio F
<x xml:space="preserve">Abstract</x> Aims Decorin and biglycan are members of the small leucine‐rich proteoglycan family, and constituents of both the extracellular matrix (ECM) and the cell surface. They are recognized as important factors in the control of proliferation, migration and invasion in vivo and in vitro. In this study, the localization patterns of decorin and biglycan were determined in healthy placentas and in highly invasive placental pathologies. Methods and results The study included immunolocalization of decorin and biglycan in samples of first‐trimester and term placentas, placenta accreta, invasive mole, and choriocarcinoma. Extravillous cytotrophoblast (EVT) cells were positive for both proteoglycans in all pathologies and in first‐trimester placentas, although not in term placentas. Biglycan was immunolocalized in the ECM of all healthy and pathological placentas, whereas decorin was observed only in term placenta ECM. Conclusions The expression of both proteoglycans was cell‐specific and gestation time‐dependent in healthy placentas, and was associated with invasive EVT cells in pathological placentas. In view of the biological properties of these molecules, it is possible that the biglycan pattern found here is intrinsically implicated in the invasive activity of EVT cells in both healthy and disordered placentas.